Assessing the impact of a carbon tax in Ukraine. (3rd April 2017) - Frey, Miriam
Abstract : Ukraine has one of the highest levels of CO2 emissions per gross domestic product (GDP) in the world. However, the country committed itself to reduce emissions from stationary sources. To this end, the Ukrainian government passed a law to impose a carbon tax on the use of energy commodities, with a current tax level of 0.26 Ukrainian Hryvnia (UAH) per tCO2 (US 0.02 per tCO2 ). Against this background, it is questioned whether such a low tax level can be expected to have any impact on CO2 emissions at all and which tax level would be consistent with the policy goal of a 22% emission reduction compared with 2007. Thus, using a computable general equilibrium (CGE) model for Ukraine, this article assesses the impact of different carbon tax levels on the Ukrainian economy and the environment. The results confirm that the effects of the current tax level are negligible. In order to achieve the reduction target a carbon tax of around UAH 40 per tCO2 (US 3.46 per tCO2 ) would be necessary. Furthermore, there is also evidence for a strong double dividend. Policy relevance Similar to Ukraine, most of the former Soviet Union countries in Eastern Europe and Central Asia have traditionally been very energy intensive. Accordingly, they are also among the highest polluters in the world. However, the case of Ukraine shows that even a relatively low carbon tax could reduce the use of energy and emissions significantly. In this respect, the present article might serve as a motivation also for those countries to work on energy-saving and climate-protection policies.